Significance of microvascular density (MVD) in cervical cancer recurrence. Issue 6 (1st October 2003) - Cantu De León, D.; Lopez-Graniel, C.; Mendivil, M. Frias; Vilchis, G. Chanona; Gomez, C.; Salazar, J. De La Garza
Abstract : The purpose of this retrospective study of 118 patients with squamous cell cervical cancer from January 1990 to December 1993 was to evaluate angiogenesis as predictive factor of recurrence in cervical cancer stages II–III treated with standard radiotherapy. Microvessel density (MVD) was evaluated and correlated with other prognostic factors. MVD was greater than 20 in 67.8% of patients with recurrence ( P = 0.002) in comparison to 39% of patients without. Disease-free survival was shorter in stage IIA and MVD >20 ( P = 0.0193) as well as for stage IIB ( P < 0.05), but not for IIIB ( P = 0.1613). Global survival was significantly shorter when MVD was >20 ( P = 0.0316). For stage IIA and MVD >20 survival was shorter ( P = 0.0008) for stage IIB ( P < 0.05) but not for IIIB ( P = 0.14). Patients younger than 40 years and MVD >20 had poorer disease-free interval and survival ( P = 0.0029). MVD in patients with squamous cell cervical cancer stage II and age younger than 40 may play a role in predicting recurrence and survival.